Pemahaman Bahasa Arab ‘Ammiyah Sebagai Strategi Dalam Menguatkan Interaksi Jamaah Umrah Indonesia di Tanah Suci - Nurbaiti, Nurbaiti (Jurnal Seumubeuet, 2025)
The Arabic ‘ammiyah dialect represents the everyday spoken language widely used by Arab communities, including those in the holy cities of Makkah and Madinah. For Indonesian umrah pilgrims, understanding this dialect plays a crucial role in facilitating communication and social interaction during their pilgrimage. However, most pilgrims focus primarily on mastering fusha Arabic, which is formal and less applicable to daily social contexts. This study aims to analyze the role of ‘ammiyah comprehension as a strategic approach to strengthening the interaction of Indonesian umrah pilgrims in the Holy Land. The research adopts a library research methodology by reviewing academic literature related to Arabic linguistics, intercultural communication, and umrah pilgrim education. The findings indicate that proficiency in ‘ammiyah enhances pilgrims’ confidence, independence, and quality of interaction with local communities. Mastering this conversational language also helps overcome communication barriers, strengthens spiritual dimensions, and enriches the overall religious experience. The study concludes that ‘ammiyah learning should be integrated into pre-departure umrah training programs in Indonesia. This research contributes not only to the development of Arabic language education but also to the broader discourse on cross-cultural religious communication aimed at improving the spiritual and social quality of Indonesian pilgrims in the Holy Land.